Problemas na linguagem e descompasso na inclusão escolar - Dudas, Tatiana Lanzarotto (2016)
The growing number of students with disabilities issues has challenged schools, teachers, especially those that act as support in regular education. Usually, these students present difficulty or absence of speech what commit on establishing bond with each other and affect the process of teaching in school. Despite this finding, focus on language and its impact on school life these kids haven’t received enough attention, often them assigns to organic or mental framework. In fact, there have been placed emphasis on the importance of involving alternative forms of communication in order to “make it feasible” them with features built in the area of Supplementary and alternative communication system (ACS). The objective is, above all, educational inclusion, more than social. This thesis leads us to a discussion of the centrality of language on the issue of inclusion in regular education of people with physical disability and who do not speak. Mobilize my experience in training courses for educators in the area of alternative communication and also my experience in particular sessions and to long-stay institutions that, by definition, are trademarks of "exclusion". The absence of "speech", often in severe cases of Cerebral Palsy (CP), has led to the assumption that if the subjects doesn’t speech, it is out of the language. It is assumed, in this thesis, the decisive force of language: the incidence of interpretation about the baby's body, inclusion in the sphere of human beings and responsible for the Constitution of this body in “parlête’s body” (Lacan’s expression). In this work are central, therefore: (1) the recognition of the order's own language (SAUSSURE, 1916), and (2) the recognition of the subject of the unconscious, introduced by Freud and formulated by Lacan. The theoretical perspective pursued in this work is being developed in the CNPq research group: Acquisition, pathologies and language clinic (LAEL-PUC-SP), coordinated by Prof. Dr. Maria Francisca Lier-DeVitto and Prof. Dr Lúcia Arantes